Strategi Pengembangan Wisata Kuliner Berbasis Masyarakat di Rungkut Surabaya - Fiqriena Anggun Tyastity; Yustisia P. Mbulu (Fakultas Pariwisata Universitas Pancasila, 2019)
The purpose of this research was to identify the culinary tour in Rungkut Surabaya, to analyze the public participation in the development of culinary tour of mangrove in Rungkut Surabaya and to identify development strategies culinary tour mangrove in Rungkut Surabaya. The existing development strategy can be a material consideration for mangrove or nature tourism Manager for mangrove culinary Manager. The design of this research uses descriptive method with the method mix proportion of qualitative methods is more dominant. To determine the strategy for the development of community- based culinary tourism in Rungkut Surabaya by using SWOT analysis. Based on the results of the SWOT analysis is obtained the results of the development strategies of community-based culinary tourism in Rungkut Surabaya i.e., among others: (1) to reproduce more human resources due to a product that has possess the raw material is seasonal (2) Increase thoroughness in providing product information to avoid the presence of the consumer that will produce processed independently (3) to make the activities of socialization for tourists in order to reduce the damage doneby tourists.